# Solve system of equations and examine how many solutions have? x+i*y=-1 2x+3y=3i

### 1 Answer | Add Yours

You may use substitution method, hence, you may use the first equation to express x in terms of y, such that:

`x = -1 - i*y`

Replacing `-1 - i*y` for `x` in the bottom equation, yields:

`2(-1 - i*y) + 3y = 3i`

`-2 - 2i*y + 3y = 3i`

You need to keep the terms that contain y to the left side, such that:

`y(-2i + 3) = 3i + 2 => y = (3i + 2)/(3 - 2i)`

`y = ((3i + 2)(3 + 2i))/((3 - 2i)(3 + 2i))`

`y = ((3i + 2)(3 + 2i))/(9 - 4i^2)`

Replacing `-1` for `i^2` yields:

`y = ((3i + 2)(3 + 2i))/13 => y = (9i + 6i^2 + 6 + 4i)/13`

`y = (9i -6 + 6 + 4i)/13`

`y = (13i)/13 => y = i`

Replacing `i` for `y` in equation `x = -1 - i*y` yields:

`x = -1 - i*i => x = -1 - i^2 => x = -1 + 1 => x = 0`

**Hence, evaluating the solution to the system of equations, yields that the system has the unique solution **`x = 0, y = i.`